Bilateral sacroiliitis and left hip arthritis secondary to isotretinoin treatment - Kulaklı, Sevgi; Kulaklı, Fazıl; İlhanlı, İlker; Tatlı, Samet; Çelik, Canan (The European Research Journal, 2019)
No abstract available.